Quantitative Quality Analysis of Scientific Software - Case Study - Koteska, Bojana; Simjanoska, Monika; Mishev, Anastas (CEUR-WS.org, 2018)
In this paper we make quantitative analysis of software for calculating ECG-derived heart rate and respiratory rate. The focus of the paper is to provide insight into the importance of the development process through a quantitative quality prism with the aim to stress the importance of the quality aspect of the code and not just the accuracy aspect. The results confirm that the ad-hoc development of a software leads to non-satisfactory results for the quality metrics and attributes of the software. Some of the main weaknesses of the code refer to cyclomatic complexity, blocks duplication, and consecutive failures.